2016
DOI: 10.5812/pedinfect.35495
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Zataria multiflora Extract Syrup and Diphenhydramine in the Treatment of Common Cold-Induced Cough in Children: A Double-Blind, Randomized, Clinical Trial

Abstract: Background: Management of cold-associated cough is a challenging aspect of supportive care for the common cold for pediatricians and parents worldwide. Herbal compounds have traditionally been used for the treatment of cold-related cough. Among these compounds, Zataria multiflora (ZM) has been found to be effective for cough relief. Objectives: The aim of this study is to compare a thyme mixture with diphenhydramine in the treatment of cold-related cough in a double-blind, randomized, clinical trial. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…19 The results of a clinical trial also indicated that treatment with Z. multiflora for 5 days led to improvement in respiratory symptoms because of the common cold in children aged 2-12 years compared with the diphenhydramine compound. 6 The current results also showed that a 2-month treatment with 2 doses of Z. multiflora extract resulted in increased FEV 1 , whereas it did not show a significant effect on MMEF. The results of clinical trials performed on asthmatic patients and sulfur mustard-exposed veterans confirmed the findings of the present study.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…19 The results of a clinical trial also indicated that treatment with Z. multiflora for 5 days led to improvement in respiratory symptoms because of the common cold in children aged 2-12 years compared with the diphenhydramine compound. 6 The current results also showed that a 2-month treatment with 2 doses of Z. multiflora extract resulted in increased FEV 1 , whereas it did not show a significant effect on MMEF. The results of clinical trials performed on asthmatic patients and sulfur mustard-exposed veterans confirmed the findings of the present study.…”
Section: Discussionsupporting
confidence: 56%
“…In a previous study, Z. multiflora similarly improved respiratory symptoms such as cough and wheezing during the day and during exercise in asthmatic patients after a 2‐month treatment, which supports the results of the current study 19 . The results of a clinical trial also indicated that treatment with Z. multiflora for 5 days led to improvement in respiratory symptoms because of the common cold in children aged 2‐12 years compared with the diphenhydramine compound 6 …”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…There are some clinical reviews that confirmed the efficacy of different formulations from Z. multiflora extract and essential oil in the treatment of acute cough (Hosseini et al, 2016;Mahboubi, 2018aMahboubi, , 2018b.…”
Section: Clinical Evidencementioning
confidence: 99%